Historical aspects of etiopathogenesis and treatment of syphilitic infection in Russia (report I) - Vyacheslav V. Chebotarev; Mikhail A. Zemtsov; Aleksei V. Odinets; Natalia V. Chebotareva (State Scientific Center of Dermatovenereology and Cosmetology, 2020)
In the historical aspect, experimental studies conducted by domestic and foreign researchers on the study of T. pallidum are presented. The incubation period and its progress through the lymphatic and circulatory pathways are established. We studied the clinical manifestations of syphilis in monkeys and rabbits corresponding to the stage manifestation in a patient with syphilis. The nature of immunity, concepts of super-and reinfection, hidden forms of syphilis, generalization of infection with damage to the nervous, cardiovascular system and visceral organs. Drugs for the treatment of patients with syphilis in the pre-penicillin period are highlighted.